PENGARUH TANGIBILITY DAN FAKTOR LAINNYA TERHADAP FINANCIAL DISTRESS DI PERUSAHAAN MANUFAKTUR - MUNGNIYATI MUNGNIYATI; ANGELICA HOLIVIN (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
This study aims to examine the effect of profitability, financial leverage, tangibility, liquidity, operating capacity, firm size, cash flow, and board independence on financial distress in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. Financial distress is measured using the Altman Z-Score formula, while the influence of independent variables is analyzed through multiple linear regression and classical assumption testing. The sample was obtained through purposive sampling from 121 manufacturing companies, with data sourced from financial statements and annual reports. This study finds that profitability, liquidity, and operating capacity have an effect on financial distress with a positive relationship. The variables of financial leverage, tangibility, firm size, cash flow, and board independence do not show any influence on financial distress. These findings can serve as a consideration for management and investors in evaluating distress risk and company stability.